1998
DOI: 10.1093/treephys/18.8-9.607
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and photoprotection in Quercus ilex resprouts after fire

Abstract: Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
47
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
12
47
0
2
Order By: Relevance
“…Mean values of midday potential quantum yield of PS II , (F v / F m ) were also similar for all kinds of treatment (0.7 ± 0.01) (figures 3g,h and figures 4g,h) and only slightly lower than reported pre-dawn values for this species (0.78) [17]. The lack of differences in F v / F m between inoculated and control plants denoted that light processing structures in PS II were not affected by infection.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Mean values of midday potential quantum yield of PS II , (F v / F m ) were also similar for all kinds of treatment (0.7 ± 0.01) (figures 3g,h and figures 4g,h) and only slightly lower than reported pre-dawn values for this species (0.78) [17]. The lack of differences in F v / F m between inoculated and control plants denoted that light processing structures in PS II were not affected by infection.…”
Section: Discussionsupporting
confidence: 61%
“…After these measurements, leaves were wrapped in aluminium foil to measure dark-adapted fluorescence: F o , F m and F v / F m (potential quantum yield of PS II equivalent to (F m -F o ) / F m )). The adaptation time was at least 20 minutes, after which values of F v / F m reach about 95% of pre-dawn ones in Q ilex [17]. Data were corrected for changes in measuring light intensity induced by temperature changes in the Mini Pam.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species show different aboveground and belowground characteristics responsible for their survival, growth, and reproduction in different habitats. There is broad evidence supporting a correspondence between the various root system traits developed by species in drought-prone ecosystems and their performance (Davis et al 1999;Bell 2001;Verdaguer and Ojeda 2002), with important implications on the extent of fluctuations in water status of species (Fleck et al 1995(Fleck et al , 1998. In addition, it has been reported that the first summer rainless period after seedling establishment is a major limiting factor when seedling roots are not fully developed (Vallejo et al 1999;Pratt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Resprouts after any of these events show decreased shoot/root ratios, which makes more water and nutrients available to the shoot than in the original plants and favours photosynthesis stimulation and rapid growth (Fleck et al, 1998). Q. ilex is exposed to multiple environmental stress factors such as drought, heat shock, chilling, nutrient deprivation and high light stress amongst others.…”
Section: Introductionmentioning
confidence: 99%